2022
DOI: 10.3390/nu14030613
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Reduces Neurotransmission, Synaptic Plasticity, and Spontaneous Hippocampal Rhythms in In Vitro Slices

Abstract: Ascorbic acid (AA; a.k.a. vitamin C) is well known for its cellular protection in environments of high oxidative stress. Even though physiological concentrations of AA in the brain are significant (0.2–10 mM), surprisingly little is known concerning the role of AA in synaptic neurotransmission under normal, non-disease state conditions. Here, we examined AA effects on neurotransmission, plasticity and spontaneous network activity (i.e., sharp waves and high frequency oscillations; SPW-HFOs), at the synapse bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…These changes were independent of changes in neurotransmitter release probability or changes in the relative contribution of AMPA and NMDA receptors. Further analysis of the tri-synaptic hippocampal circuit by measuring the population field potential (excitatory postsynaptic potential, EPSP) via Schaffer-collateral stimulation evoked EPSP, sharp wave, and high-frequency oscillation in acute hippocampal slices could provide insight into the impact of Nrxn2 deletion on overall hippocampal network activity [63,64]. Moreover, a recent study suggested a canonical regulatory role of neurexins on presynaptic GABA B receptor mediated function on glutamatergic transmission and release probability [8].…”
Section: Discussionmentioning
confidence: 99%
“…These changes were independent of changes in neurotransmitter release probability or changes in the relative contribution of AMPA and NMDA receptors. Further analysis of the tri-synaptic hippocampal circuit by measuring the population field potential (excitatory postsynaptic potential, EPSP) via Schaffer-collateral stimulation evoked EPSP, sharp wave, and high-frequency oscillation in acute hippocampal slices could provide insight into the impact of Nrxn2 deletion on overall hippocampal network activity [63,64]. Moreover, a recent study suggested a canonical regulatory role of neurexins on presynaptic GABA B receptor mediated function on glutamatergic transmission and release probability [8].…”
Section: Discussionmentioning
confidence: 99%
“…25 Ascorbic acid (AA) is a water-soluble vitamin that functions as an antioxidant, serves as a cofactor in several enzymatic reactions, and participates in some synthetic pathways in higher primates. 28 It exists as the anion ascorbate (see Fig. 2c) and is a powerful reducing agent at physiological pH.…”
Section: Naela Delmo Bahar Mostafiz Johanna Suni and Emilia Peltolamentioning
confidence: 99%